Assessment Of Safe Load On Piles Using Indian Standard Codeprivate ? Synopsis - Shenbaga R. Kaniraj (Deep Foundations Institute, 1996)
The pile loading tests are generally conducted to assess the safe load on piles in compression. In the Indian practice, the safe load is determined using the pile loading test data and the two criteria specified in the Indian Standard Code, IS.2911 (Part 4) -1985. For this, the test pile should have undergone a minimum displacement equal to 10% of the pile diameter. Often, the piles are not subjected loads that are sufficient to cause a displacement of this magnitude. If the settlement is at least 12 mm, then the safe load is determined based only on the first criterion. But, if the settlement is less than 12 mm, the safe load cannot be determined using the IS Code criteria. The paper presents two procedures called hyperbolic and generalized hyperbolic methods to estimate the safe load using the IS Code criteria even when the loading test data is insufficient. The data from two initial tests have been analyzed. The predicted safe loads have been compared with the actual safe loads.